THE ANALYSIS OF STUDENTS’ CHALLENGES TO THESIS WRITING AT UIN ALAUDDIN MAKASSAR - Citra Dwi Safitri; Siti Azisah; Muhammad Jabal Annur (Universitas islam Negeri Alauddin Makassar, 2021)
Thesis writing as one of final year students’ assignment is not a simple work. It involves hard work and effort to complete. This research addresses issue of the students’ challenges to thesis writing among the eighth semester students of English Education Department at UIN Alauddin Makassar. The research questions were asking about the challenges faced by the eighth semester students to thesis writing of English Education Department at UIN Alauddin Makassar and the causal factors of the challenges faced by the eighth semester students to thesis writing of English Education Department at UIN Alauddin Makassar. Descriptive qualitative design was used in this research. The subject of this research consisted of 30 students of English Education Department intake year 2016. The subjects were chosen purposively including several criteria. The data of this research was obtained from two kinds of instruments, namely interview with supporting data from questionnaire. The data analysis technique in this research used three steps, they are identification, classification, and explanation. The result of this research showed that the students mostly encountered challenges and delays in their thesis writing process. The challenges were: lack of availability of the references and resources related to the students’ thesis topic, lack of students’ skills in research methodology, as well as lack of students’ knowledge related to the guidelines for writing scientific paper. Moreover, the challenges that the students encountered divided into two affecting factors, namely internal factor and external factor. The internal factors of the students’ challenges are the students’ academic skill related to research methodology and guidelines for writing scientific paper; and the students’ self-confidence. Whereas, the external factors that influencing the students’ challenges are, the availability of the research references, research supervisor, as well as respondents.